LIVESTOCK SELF-SUFFICIENCY AND LIVESTOCK HOUSEHOLD DISTRIBUTION IN INDONESIA: CURRENT STATE AND EXPECTED DEVELOPMENTS - Adhi Susilo; Deddy Ahmad Suhardi (AgriDev, 2022)
Indonesia has increasing demand for animal sources of food including red meat. There has always been a national gap between supply and demand of red meat. This paper aims to describe the current features and prospects for livestock production systems in Indonesia. The research method used is descriptive statistics. Based on the source, the data used in this study is secondary data from the Central Statistics Agency (BPS). The first part of the article reviews and analyses population of Indonesian livestock. The second part addresses issues related to the current distribution of livestock that could become important for future development of the livestock industry in Indonesia. Recommendations to improve distribution, to empower smallholder farmers, and to develop systems for livestock development are briefly discussed.